2006
DOI: 10.1097/01.rhu.0000221817.46231.18
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Fibromyalgia and Its Associated Comorbidities

Abstract: Females are more likely to be diagnosed with fibromyalgia than males, although to a substantially smaller degree than previously reported, and there are strong associations for comorbid conditions that are commonly thought to be associated with fibromyalgia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(60 citation statements)
references
References 19 publications
(23 reference statements)
3
55
1
1
Order By: Relevance
“…1988), while fibromyalgia, epilepsy, and IHD are associated with increased prevalence of both depression and anxiety disorders (Weir et al. 2006; Tellez‐Zenteno et al. 2007; Janssens et al.…”
Section: Discussionmentioning
confidence: 99%
“…1988), while fibromyalgia, epilepsy, and IHD are associated with increased prevalence of both depression and anxiety disorders (Weir et al. 2006; Tellez‐Zenteno et al. 2007; Janssens et al.…”
Section: Discussionmentioning
confidence: 99%
“…Relative risk ratios (RR) between FM and OA and FM and control samples were calculated based on the proportion in each sample with comorbid conditions. 2 tests were used to compare between-sample differences for dichotomous or categorical variables, and t tests were used to compare continuous variables with minimal skewness in the distribution. Differences in continuous measures of utilization and costs were compared using nonparametric Wilcoxon ranksum tests.…”
Section: Methodsmentioning
confidence: 99%
“…3 The majority of studies on FM acknowledge the gender differences within the prevalence rates, such that women are 7 to 10 times more likely than men to be diagnosed with FM. [8][9][10] The symptoms of FM often overlap with other conditions thought to be "psychosomatic," such as chronic fatigue syndrome, 11 chronic headache, [12][13][14] irritable bowel syndrome, [15][16][17] and temporomandibular joint disorder. 18,19 Many studies have found strong associations with psychosocial distress, specifically depression, in FM populations.…”
mentioning
confidence: 99%